The Encyclopedia of Child and Adolescent Development 2020
DOI: 10.1002/9781119171492.wecad218
|View full text |Cite
|
Sign up to set email alerts
|

Only Children

Abstract: Only children are children who grow up without siblings. They are assumed to be deficient because they do not have the experience of growing up with siblings. This assumption motivated many studies in the United States and, in general, these studies have found only children to score similarly to others, especially firstborns and children with one sibling, although there is evidence that only children may attain more education than others. In China, the one‐child family became a social norm in cities because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The term only children refers to individuals who grew up without siblings (Falbo, 2019). Historically, only children have been viewed as deficient by researchers, professionals, and the general public alike (Blake, 1981; Mancillas, 2006).…”
Section: Only Children In China: the Context And Stereotypementioning
confidence: 99%
See 2 more Smart Citations
“…The term only children refers to individuals who grew up without siblings (Falbo, 2019). Historically, only children have been viewed as deficient by researchers, professionals, and the general public alike (Blake, 1981; Mancillas, 2006).…”
Section: Only Children In China: the Context And Stereotypementioning
confidence: 99%
“…In the case of Chinese only children, multiple scholars from diverse fields including psychology, sociology, demography, and anthropology have reached a consensus that growing up without a sibling became a social norm in China, at least in urban areas where the OCP was strictly implemented (Falbo, 2012(Falbo, , 2019Feng et al, 2013;Gu et al, 2007;Whyte et al, 2015). Drawing from China's latest mini-census in 2005, Feng and his associates reported that the OCP has resulted in almost 80% of families in China's big urban centers having only one child, and thus proclaimed "a virtually universal one-child family world is already a reality" (p. 124).…”
Section: Loneliness and Chinese Only Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the extant literature, being the only child of a family produces both positive and negative effects on different aspects of a person’s life, including their personality development, academic attainment and mental healthiness. In some literature, it is shown that being the only child of a family is less a blessing in one’s life (Falbo, 1977). For instance, the children born after the implementation of the One-Child Policy in China had fewer opportunities to interact with others compared to their counterparts who had siblings when growing up.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The status of being an only child (as compared to birth order) presents distinct characteristics and experiences that may warrant separate examination in understanding its potential impact on CEO decision-making and behavior. For instance, one of the fundamental differences is that being an only child have all the parental resources and care, and they do not have to face the rivalry from their siblings (Falbo, 1977; Sulloway, 2001).…”
Section: Introductionmentioning
confidence: 99%